Manajemen Keuangan Keluarga untuk Mengokohkan Keutuhan Rumah Tangga - Mia Hermaliana (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
Money has an important role in human life. Especially in the family. Not only the amount of money you have, but how to use the money earned for family happiness. To be able to utilize and optimize the money that is owned so that it is more beneficial for family life. For this reason, the ability to properly manage family finances is needed. With family financial management, it is expected that the use of money in the family can be effective and efficient, effective and efficient in accordance with family needs so that the family becomes prosperous. This article discusses the description of financial management, how to do it, and who should do it.